Sexuality and sub-Saharan literatures : from the poetic of bashfulness to the aesthetic of sex - (:unkn) unknown (My University, 2019)
The colonial novel has long been the "only approach" apprehending the settlement. Unfortunately, it produced a sexual imaginary about Africa excluding the speech of the colonized. Africa is a place of pleasure, a "sexual Eden", and all the natives have "lust stuck into the body". Curiously, this imagology does not influence African literary works. Rather, Africa and its literatures have been considered as real bashful spaces. For many reasons the African author chooses avoidance strategies. He uses a series of stylistic processes to veil it, to make it seen in the absence or silences. This scriptural reserve dominates francophone literary production in sub-Saharan Africa until the 1960s. During this decade, an iconoclastic generation arises, and breaks with this representation. A more transgressive type of writing appears. Henceforth, the African authors seem to refuse the “indirection”, the roundabouts, and the narrative ellipsis. They are part of what Michel Foucault calls parrhêsia, a speech of truth. Thus, this perspective focuses on the need to say things as they are. This allows the emergence of what we call the sexualiture, which means literature giving the sex an important place. The present study examines, on the one hand, the process of this emancipating written form, linked to feminism; it analyses, on the other hand, the links between a poetic modesty as guarantor of a restrained discourse about sex, and the insolence of an authentic line expressing a legitimate pursuit of freedom.
Keywords: African Research